PHYSICAL DEVELOPMENT AND HEALTH OF SCHOOLGIRLS (Conferencea, 2023)
In this article, the main features of the indicators of physical development of schoolgirls are presented, and in general, the methodology of obtaining anthropometric indicators is covered in detail.